HUBUNGAN PERILAKU CARING PERAWAT DENGAN KEPUASAN PASIEN DIRUANG RAWAT INAP INTERNA GUNUNG JATI DAN GUNUNG GIRIRSI. SAKINAH MOJOKERTO - Lestari, Indah; Chodijah Fahmi, Nur (JURNAL KEPERAWATAN SEHAT, 2016)
Behavior of nurse caring represent is one aspect that relate to service treatment, because caring include link between human being and have an effect on to quality service and satisfaction patient. This research aim to know behavioral link nurse caring with satisfaction patient take care to stay in unit of internal room Sunan Gunung Jati and Sunan Giri RSI Sakinah Mojokerto . This Research use correlation analytic design, approach sectional cross. Becoming sample is patient internal room Sunan Gunung Jati and Sunan Giri RSI Sakinah Mojokerto, counted 40 people. Intake sample with technique consecutive sampling. Data collected to through kuisioner structure. Test correlation Spearman used to test behavioral link nurse caring with storey satisfaction patient. Result of research indicate that there is significan between behaviour nurse caring with storey satisfaction patient to take care to lodge. Test corelation Spearman show p value = 0,000 < 0,05. Inferential that there is link which is significan between behavior nurse caring with storey satisfaction patient take care to lodge unit of internal room Sunan Gunung Jati and Sunan Giri RS. Sakinah MojokertoKeyword : behavioral of nurse caring and satisfaction patient